2004
DOI: 10.1128/aem.70.11.6512-6517.2004
|View full text |Cite
|
Sign up to set email alerts
|

No Significant Contribution of Arbuscular Mycorrhizal Fungi to Transfer of Radiocesium from Soil to Plants

Abstract: The diffuse pollution by fission and activation products following nuclear accidents and weapons testing is of major public concern. Among the nuclides that pose a serious risk if they enter the human food chain are the cesium isotopes 137 Cs and 134 Cs (with half-lives of 30 and 2 years, respectively). The biogeochemical cycling of these isotopes in forest ecosystems is strongly affected by their preferential absorption in a range of ectomycorrhiza-forming basidiomycetes. An even more widely distributed grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 29 publications
(29 reference statements)
1
24
2
Order By: Relevance
“…This contrasts with the findings of Joner et al (2004) who recently concluded that arbuscular mycorrhizal fungi are unlikely to have any significant effect on Cs uptake by plants. However, other studies, including some on tree species, are less categorical.…”
Section: Mycorrhizal Association and Radionuclide Dynamicscontrasting
confidence: 82%
“…This contrasts with the findings of Joner et al (2004) who recently concluded that arbuscular mycorrhizal fungi are unlikely to have any significant effect on Cs uptake by plants. However, other studies, including some on tree species, are less categorical.…”
Section: Mycorrhizal Association and Radionuclide Dynamicscontrasting
confidence: 82%
“…Indeed, depending on the plant and AM fungal species and on the experimental conditions, the accumulation of radiocesium in mycorrhizal plants can be lower (Dighton and Terry, 1996;Berreck and Haselwandter, 2001), similar (Rogers and Williams, 1986;Rosén et al, 2005) or even higher (Mc Graw et al, 1979;Entry et al, 1999;Rosén et al, 2005) than in non-mycorrhizal plants. However, as noticed by Joner et al (2004), the experimental setups used in these studies did not assess fungal transport or immobilization, but rather the combined effect of AM fungi and root uptake on plant radiocesium accumulation. In addition, the participation of AM fungi in the immobilization or transport of radiocesium could not be evaluated by the sole observation of its accumulation in plants as plant-AM fungus associations and experimental conditions influenced plant growth and root-to-shoot biomass partition resulting in the well-known ''dilution effect'' (Timmer and Leyden, 1980;Smith and Read, 1997;Clark and Zeto, 2000).…”
Section: Am Fungimentioning
confidence: 97%
“…However, neither the concentrations of K nor radiocesium in the soil solution were measured in these experiments. Joner et al (2004) concluded that arbuscular mycorrhizas are unlikely to play any significant role in plant radiocesium acquisition through the process of fungal transport, especially in agricultural ecosystems. However, Dupré de Boulois et al (2005b) suspected that the uptake of radiocesium by AM fungi in this study could have been strongly impaired by the sorption capacity of clay, the bio-availability of K in the soil solution and/or plant K nutritional status.…”
Section: Transport and Immobilization Of Radiocesium By Am Fungimentioning
confidence: 98%
See 1 more Smart Citation
“…Three separate experiments performed by three laboratories using different protocols and fungus/host plant combinations [19] to investigate whether AM fungi can transport Cs in soil-based systems. Here only the first experiment will be discussed.…”
Section: Role Of Mycorhizal Fungi In Radiocaesium Accumulation In Plantmentioning
confidence: 99%